Dik Oi Aquatic Enterprise / Azizul Zekri Abd Rahim ... [et al.] - Abd Rahim, Azizul Zekri; Hussain, Mohamad Fauzi; Mat Nawi, Mohd Azrani; Abdullah, Mohd Azrul (2003)
Dik Oi Aquatic Enterprise is the business where provide the process of supplying, packaging and selling the prawns as fish food to the wholesaler. However, we are willing to accept any orders from our customers in order to fulfill the demanding of fish as pets market. Our business form is a partnership form. We have four very important persons who are involved in the born of Dik Oi Aquatic Enterprise. The first one is Mr. Azizul Zekri Abd Rahim as our General Manager and he is our Administration Manager too, Mr. Fauzi Hussain as our Marketing Manager, Mr. Mohd Azrani Mat Nawi as our Operation Manager and lastly Mr. Mohd Azrul Abdullah as our Financial Manager. We are running this business with the capital amount of RM 29385.94. Each partner contributed RM6758.77. That is 23%. Whereas the General Manager as well as the Administration Manager, he contributed RM 9109.63 with the percentage of 31%. Meanwhile, the balance of our business capital is from the bank loan. We get the loan from Bank Pertanian. The total of loan is RM 60000. Our business is located at lot 3443, 9423 and 9422, Jalan Kemenyan, Kampung Poh, 35500 Bidor, Perak. We decided to choose this location because it is situated in strategic area. In addition, the location is near and easy to get the water sources that is important to our business because we are running the business in aquatic for sure the ponds need water. Furthermore, the locations also near the road. So the customers will easy to find our office.